Holocene invertebrates from the Rocas Atoll: A contribution for the ecological history of South Atlantic islands - Soares,Marcelo de Oliveira (2016)
The South Atlantic Ocean is the youngest of the worlds oceans and one of the most important biodiversity hotspots; however, there is a lack of scientific knowledge about its ecological history. Here, we present the first results of a fossil invertebrate survey from the Rocas Atoll. By using radiometric dating (14C) and a survey of fossilized benthic invertebrates on this atoll, we provide new paleobiogeographic and paleoceanographic information. The results suggest eight taxa (five mollusks, two corals, and one decapod). Dates ranged from 3449 ± 790 y BP to 3033 ± 620 y BP. The data represent new invertebrate records for the middle Holocene in this atoll, and evidence of sea-level changes in this period. Considering that the Rocas Atoll is one of the newest marine atolls in the world, these results suggest recent colonization by species from the Southwestern Atlantic Coast and Fernando de Noronha Archipelago.